Retrospective Evaluation of Laparoscopic Versus Open Hartmann's Reversal. Issue 5 (October 2015) - Brathwaite, Shayna; Kuhrt, Maureen; Yu, Lianbo; Arnold, Mark; Husain, Syed; Harzman, Alan E.
<x xml:space="preserve">Abstract</x> Purpose: Restoration of intestinal continuity after Hartmann's procedure has significant associated morbidity. There has been a trend toward increasing utilization of laparoscopy in colorectal surgery, with improvements in short-term outcomes. This study evaluates our experience with laparoscopic Hartmann's procedure reversal. Methods: All patients who underwent laparoscopic and open reversal of Hartmann's procedure between 2007 and 2010 were reviewed. Demographics, length of stay, postoperative morbidity, and mortality were compared between the 2 groups. Results: Nineteen patients underwent laparoscopic Hartmann's reversal and 62 underwent open reversal. There were no statistically significant differences in demographics, comorbidities, mean operative times, blood loss, reoperation, and readmission rates between the groups. The laparoscopic group had a shorter length of hospitalization (5.7 vs. 7.9 d, P<0.01). Conclusions: Laparoscopic reversal of Hartmann's pouch is a safe and feasible alternative to the open reversal technique. Patients who undergo the laparoscopic technique have a shorter length of hospital stay.